Tractography passes the test: Results from the diffusion-simulated connectivity (disco) challenge - Girard, Gabriel; Rafael-Patiño, Jonathan; Truffet, Raphaël; Aydogan, Dogu Baran; Adluru, Nagesh; Nair, Veena A; Prabhakaran, Vivek; Bendlin, Barbara B; Alexander, Andrew L; Bosticardo, Sara; Gabusi, Ilaria; Ocampo-Pineda, Mario; et al. (NeuroImage, 2023)
Estimating structural connectivity from diffusion-weighted magnetic resonance imaging is a challenging task, partly due to the presence of false-positive connections and the misestimation of connection weights. Building on previous efforts, the MICCAI-CDMRI Diffusion-Simulated Connectivity (DiSCo) challenge was carried out to evaluate state-of-the-art connectivity methods using novel large-scale numerical phantoms. The diffusion signal for the phantoms was obtained from Monte Carlo simulations. The results of the challenge suggest that methods selected by the 14 teams participating in the challenge can provide high correlations between estimated and ground-truth connectivity weights, in complex numerical environments. Additionally, the methods used by the participating teams were able to accurately identify the binary connectivity of the numerical dataset. However, specific false positive and false negative connections were consistently estimated across all methods. Although the challenge dataset doesn't capture the complexity of a real brain, it provided unique data with known macrostructure and microstructure ground-truth properties to facilitate the development of connectivity estimation methods.
Keywords: metoda Monte Carlo; mozek; Humans; Connectivity; Phantoms, Imaging; Diffusion MRI; Numerical substrates; lidé; Tractography; počítačové zpracování obrazu; Image Processing, Computer-Assisted; Monte carlo simulation; difuzní magnetická rezonance; Monte Carlo Method; Microstructure; Brain; Challenge; fantomy radiodiagnostické; Diffusion Magnetic Resonance Imaging